The Cutaneous Leishmaniasis and the Sand Fly: Knowledge and Beliefs of the Population in Central Morocco (El Hajeb) - Karima El-Mouhdi; Abdelkader Chahlaoui; Mohammed Fekhaoui (Hindawi Limited, 2020)
Background. Cutaneous leishmaniasis is a neglected parasitic dermal disease transmitted to humans through the bite of an infected female sand fly. Morocco hopes to eliminate all forms of leishmaniasis by 2030. These dermatoses pose a real public health problem in the country. Although the information is available on the disease, individual knowledge of cutaneous leishmaniasis and sand fly is not yet developed. Exploring people's beliefs and popular behaviours about cutaneous leishmaniasis and its vector allows health officials to know the sociocultural aspects of the disease and to improve prevention and control actions. Objectives. To identify the knowledge of cutaneous leishmaniasis and its vector in the population in central Morocco. Methods. Based on the epidemiological data of leishmaniases in the province of El Hajeb, we conducted a field survey and personal interviews in April and May 2019, among 281 persons belonging to the localities where leishmaniases were registered. Results. Our results show that the participants use the concept of "Chniwla" (61.6%) for sand fly and the concept of "Hboub Chniwla" (50.8%) for cutaneous leishmaniasis; 24.6% of the respondents do not know how the disease is transmitted to humans and 43.7% use traditional treatments and home remedies to cure themselves. 44% of participants believe that sand fly does not transmit the disease to humans and only 6.4% were aware of their responsibility in vector control. Conclusions. The study concluded that there is a need to simplify the scientific terminology in the health education of citizens regarding these dermatoses and their vector by integrating the popular concepts obtained in this study to raise public awareness and facilitate their involvement as active actors in the prevention of cutaneous leishmaniasis.